Landasan ontologi, epistemologi dan aksiologis dalam kajian pendidikan karakter - Amalia Ngazimah; Darmiyati Zuchdi (BAHASTRA, 2020)
This study aims to reveal the foundation of ontology, epistemology and axiology in an article entitled "Analysis of the Character Education Content of the Social Studies Textbooks of Junior High Schools in Surakarta City" written by Permatasari. This research is an inferential content analysis research. namely the foundation of ontology, epistemology and axiology, or in other words what, how and where is the science. The technique used in this research is the content analysis technique. The validity and reliability in this study were intraritarian semantics (test retest reliability). The results showed that: 1) the foundation of the ontology used consisted of material objects, namely the content of character education in social studies textbooks in the city of Surabaya; 2) the epistemological foundation consists of steps 3) the axiological foundation in the form of the benefits of character education values developed in the social studies textbooks in the city of Surabaya which have ethical (religious) and moral values.